Identification of Ethnomathematics in Wat Arun “Temple of Dawn” in Bangkok, Thailand - Halim, Erwin Ardianto; Darmayanti, Tessa Eka (University of Merdeka Malang, 2025)
This qualitative descriptive research was conducted to identify ethnomathematics concepts in Wat Arun